1901 Fla. Laws 57, ch. 4928. - (:unkn) unknown (General Publisher, 1901)
Amended 1893 Fla. Laws 71, ch. 4147 to include licensing for carrying concealed handguns. Violators fined one hundred dollars or jailed for thirty days.
--
Keywords: CARRY - CONCEALED